Mengurangi Kenakalan Remaja Menggunakan Konseling Behavioral pada Peserta Didik di SMA - Maulana, Muhammad Arief; Nugroho, Panggih Wahyu (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2019)
juvenile delinquency is indeed a phenomenon that occurs at the developmental stage of adolescence. Phenomena that occur are behaviors that deviate from the norms that apply in the community such as ditching, bullying, smoking, drinking liquor, lying, and others. All behaviors carried out bby adolescents on the basis of wanting to try and be dominantly influenced by environmental factors. Juvenile delinquency reflects adolescents having difficulty finding their identity so that they experience an identity crisis. Researchers want to reduce juvenile delinquency using behavioral counseling approaches. The reason for using this counseling is because behavioral counseling is counseling which is a combination of approaches in cognitive psychotherapy therapy and behavior therapy. The type of research used is using experimental research. The design of the research in this study used was the prettest and post-test group. The pre-test results showed that students got ajuvenile delinquency score of 54.23% in the medium criteria, while the post test showed a score of 32.08 in low criteria. Based on the results of the calculation of the comparison of the pre-test and post-test scores, the average respondents experienced a decrease in juvenile delinquency by 22.15%. This proves that behavioral counseling can reduce the level of juvenile delinquency. While the wilcoxon test obtained z count of -1.82, because this value is an absolute value so that the negative sign is not taken into account. So that the calculated z value becomes 1.82, then the calculated z value is compared with the z table value with an error level of 0.05. The conclusion is that the juvenile delinquency of sma n 1 nguter can be reduced through counseling behavioral approaches.